Legal Analysis of Blood Donation in Indonesia from the Perspective of Islamic Ethics - Rusmiyanti Rusmiyanti; Aris Prio Agus Santoso; Muhamad Habib (Research of Service Administration Health and Sains Healthys, 2025)
Although blood donation in Indonesia has been regulated through various legal instruments and is regarded as a humanitarian act in Islam, numerous ethical and legal issues still arise in practice. This creates a gap between the commercialized reality of implementation and the normative expectation that blood donation should be grounded in sincerity, solidarity, and the principle of hifz al-nafs within Islamic ethics. The purpose of this study is to analyze the regulation of blood donation in Indonesia based on applicable laws and to examine the principles of Islamic ethics in viewing blood donation as a form of health and humanitarian service. This research employs a normative juridical approach with a prescriptive type of study, focusing on literature review to examine the legal framework and Islamic ethical principles in blood donation practices in Indonesia. The study uses secondary data derived from primary, secondary, and tertiary legal materials. Data collection was conducted through literature study, and the analysis applied a qualitative method to interpret legal norms, evaluate regulatory effectiveness, and formulate normative solutions. The results show that the practice of blood donation in Indonesia represents the integration of legal, moral, ethical, and humanitarian values guaranteed by the 1945 Constitution, further elaborated through Law No. 17 of 2023 and Minister of Health Regulation No. 91 of 2015, which emphasize voluntary, non-commercial, and humanitarian principles. The Indonesian Ulema Council (MUI) Fatwa No. 23 of 2019 affirms that blood donation is a virtuous act reflecting the spirit of mutual assistance. From an Islamic ethical perspective, blood donation embodies the values of hifz al-nafs and al-maslahah within maqasid al-shari‘ah, serving as a form of social worship that rejects any exploitation of the human body.